You are on page 1of 2

C1 ( t )=

1
2 2
ln |
cost 2
cost + 2 |
cost 2 cost
C2 ( t ) = C ( t )=
1 3cos 2t 2
1+sen 2 t

d(sent )
C2 ( t )= dt C2 ( t ) =arctg|sent|
sen2 t+1
Reemplazando en (1):

y p=
1
2 2
ln |
cost 2
cost + 2 |
cost +arctg|sent|sent

Si
y G= y h+ y p

y G =C 1 cost+ C2 sent
2 2
1
ln | cost 2
cost + 2 |
cost+ arctg|sent| sent

13. Resolver.
e2 x
y 3 y +2 y=
1+ e2 x
Solucin.-
y 3 y +2 y=0 ( D 23 D+2 ) y=0

r 23 r +2=0
( r1 ) ( r2 )=0 r=1 y r=2
x 2x x 2x
y h=C 1 e +C 2 e y 1 ( x )=e ; y 2 ( x )=e
x
para y p por funcin de : y p= G ( t , x ) f ( t ) dt
xo

y p=
|
x | e t e2 t
e x e2 x e 2t
x
e x et (e x et ) e 2 t
dt y p= 3 t dt
1+e 2 t e ( 21) 1+ e2 t
| |
xo e t e2 t
e t 2e 2 t
x o

x 2x x t x x t
e e e 1 e
y p= 2t
dt=e 2 x 2t
dte x 2t
dt
x 1+e o
x 1+e x 1+e o o
e
t
d (e )
2
si e2 t =u ;2 e2t dt=du
1+( t)
x x
2x e2t x
y p=e 2 t dte
x e +1
o x o

| |
x x t
1 du d(e ) 2x 1 1+e 2 x
y P =e e x
2x
t
=e ln 2x
e x arct g( e x )
x u+1 2
o
x 1+ e o
2 e

1
donde y p =e x arctg ( e x ) + x e 2 x e 2 x ln |1+e 2 x|
2
si y G = y h+ y p

x 2x x x 2x 1 2x 2x
y G =C 1 e + C2 e e arctg ( e ) + x e e ln |1+e |
2